Tanggung Jawab Pelaku Usaha Rokok Yang Tidak Mencantumkan Informasi Dan Peringatan Kesehatan Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Salukh, Andre; Nubatonis, Orpa J; Pello, Helsina F (Law Faculty, Nusa Cendana University, 2024)
This study analyzes the responsibilities of tobacco businesses that fail to include health information and warnings in accordance with Law No. 8 of 1999 on Consumer Protection. The objective of this research is to identify the legal implications and consequences for businesses that neglect these obligations. The methodology employed is quantitative analysis through data collection. The results indicate that non-compliance with the requirement to provide health information and warnings can lead to administrative sanctions and legal claims. Additionally, the lack of information poses health risks to consumers and infringes upon their rights. This research concludes that stricter law enforcement is essential to protect consumers and encourage businesses to fulfill their responsibilities.